METHODOLOGICAL FOUNDATIONS AND PEDAGOGICAL TECHNOLOGIES OF DISTANCE TEACHING IN UNIVERSITIES - Kunnazarov Aliy Bisenbayevich (Bright Mind Publishing, 2025)
The article analyzes the methodological foundations and pedagogical technologies of distance learning (DL) in higher educational institutions (HEIs). Issues of didactic principles, design of educational content, organization of the educational process, and assessment of student mastery based on the combination of modern information and communication technologies (ICT) and pedagogical methods are considered. Ways to improve the quality of education, develop students' independent learning skills, and accelerate the digital transformation of higher education institutions through the effective use of pedagogical technologies are proposed.
Keywords: Distance learning, methodology, pedagogical technologies, ICT, didactics, quality of education, independent learning, digital transformation, higher education.